The Effect of Preoperative Pulmonary Arterial Hypertension on Incidence of Postoperative Atrial Fibrillation after Surgical Closure of Atrial Septal Defect (Secundum) (University Heart Journal, 2018)
Background: Atrial tachyarrhythmias are common among adults with ASD and contribute to substantial morbidity. Atrial flutter and atrial fibrillation are well-described complications of atrial septal defect (ASD) and are associated with substantial morbidity. The cause of AF in ASD is multifactorial in nature. It has been proposed that it is related to atrial dilatation, the increase in pulmonary pressure, and ventricular dysfunction. Early surgical intervention may reduce the long-term risk of developing atrial arrhythmias. Studies demonstrated that cardiac remodeling occurred after closure of an ASD, even in older patients. This study aimed to find out the pulmonary hypertension (PAH) as a predictor of postoperative atrial fibrillation in patients after surgery for secundum type atrial septal defect closure.Methods: This Prospective Observational Study carried out in department of cardiac surgery, National Institute of Cardiovascular Disease (NICVD) and Hospital, Dhaka, Bangladesh during the period of July, 2015 to June, 2016. Total 54 patients are taken and then grouped into group A and group B. Each group contains 27 patients. Group A include Patients with ASD secundum without PAH. Group B Patients with ASD secundum with PAH. All patients were evaluated with M-mode, 2D and color Doppler transthoracic echocardiography and ECG before operation, at discharge, after one month and at 3 months follow-up. Statistical analysis of the results was obtained by windows based computer software with statistical package for the social sciences program (SPSS version 21).Results: To compare atrial fibrillation postoperative at discharge and postoperative after 1 and 3 months follow-up it was found In group B 8 (29.62%) patients had AF postoperatively, during discharge 8 (29.62%) patients had AF, after 1 month 7 (25.93%) patient had AF, after 3 months 6 (22.22%) patients had AF. No AF was found in Group A patients during postoperatively, during discharge, after 1 month & 3 months follow up. Statistical significant difference was found in between two groups (p